Supervisor Efforts to Improve Service Quality and Guest Satisfaction at Makase Restaurant at Hotel Indigo Bali Seminyak Beach - Nugraha, Surya; Rusmiati, Nyoman (Akademi Komunitas MAPINDO, 2023)
This study aims to determine the efforts of supervisors in improving service quality and guest satisfaction at Makase Restaurant at Hotel Indigo Bali Seminyak Beach, where this research has the formulation of the problem, (1) Supervisor's efforts to improve service quality and guest satisfaction at Makase Restaurant at Hotel Indigo Bali Seminyak Beach, (2) What constraints are faced by supervisors in efforts to improve service quality and guest satisfaction at Makase Restaurant at the Indigo Bali Seminyak Beach Hotel, and (3) How supervisors overcome obstacles in an effort to improve service quality and guest satisfaction at Makase Restaurant at Hotel Indigo Bali Seminyak Beach. This research uses qualitative research methods with primary data sources and secondary data. Data collection techniques by direct observation at the Makase Restaurant, interviews with supervisors regarding the supervisor's efforts to improve service and guest satisfaction at the Makase Restaurant, and documentation by taking pictures using a mobile phone. The research instruments used were recording equipment, interview lists, notebooks and laptops. The analysis presentation technique used is descriptive, by obtaining data obtained from research on supervisors' efforts to improve service quality and guest satisfaction at Makase Restaurant. The result of this study is that the supervisor's efforts have an important role in improving service quality and guest satisfaction in restaurants. Keywords: Effort, Supervisor, Improve, Quality, Service, Satisfaction.